A standardized blood test for the routine clinical diagnosis of impaired GM-CSF signaling using flow cytometry - Kusakabe, Yoshiomi; Uchida, Kanji; Hiruma, Takahiro; Suzuki, Yoko; Totsu, Tokie; Suzuki, Takuji; Carey, Brenna C.; Yamada, Yoshitsugu; Trapnell, Bruce C. (Journal of immunological methods, 2014)
Impaired signaling by granulocyte/macrophage-colony stimulating factor (GM-CSF) drives the pathogenesis of two diseases (autoimmune and hereditary pulmonary alveolar proteinosis (PAP)) representing over ninety percent of patients who develop PAP syndrome but not a broad spectrum of diseases that cause PAP by other mechanisms. We previously exploited the ability of GM-CSF to rapidly increase cell-surface CD11b levels on neutrophils (CD11bSurface) to establish the CD11b stimulation index (CD11b-SI), a test enabling the clinical research diagnosis of impaired GM-CSF signaling based on measuring CD11bSurface by flow cytometry using fresh, heparinized blood. (CD11b-SI is defined as GM-CSF-stimulated- CD11bSurface minus unstimulated CD11bSurface divided by un-stimulated CD11bSurface multiplied by 100.) Notwithstanding important and unique diagnostic utility, the test is sensitive to experimental conditions that can affect test performance. The present study was undertaken to optimize and standardize CD11b-SI test for detecting impaired GM-CSF signaling in heparinized human blood specimens from PAP patients. Results demonstrated the test was sensitive to choice of anticoagulant, pretesting incubation on ice, a delay between phlebotomy and test performance of more than one hour, and the concentration GM-CSF used to stimulate blood. The standardized CD11b-SI test reliably distinguished blood specimens from autoimmune PAP patients with impaired GM-CSF signaling from those of health people with normal signaling. Intra-subject differences were smaller than inter-subject differences in repeated measures. Receiver operating characteristic curve analysis identified a CD11b-SI test result of 112 as the optimal cut off threshold for diagnosis of impaired GM-CSF signaling in autoimmune PAP for which the sensitivity and specificity were both 100%. These results support the use of this standardized CD11b-SI for routine clinical identification of impaired GM-CSF signaling in patients with autoimmune PAP. The CD11b-SI may also have utility in clinical trials of novel therapeutic strategies targeting reduction in GM-CSF bioactivity now under evaluation for multiple common autoimmune and inflammatory disorders.